2019
DOI: 10.2147/idr.s203543
|View full text |Cite
|
Sign up to set email alerts
|

<p>Diagnostic performance of direct latex agglutination, post-enrichment latex agglutination and culture methods in screening of group B streptococci in late pregnancy: a comparative study</p>

Abstract: BackgroundGroup B streptococcus (GBS) is one of the main causes of neonatal sepsis.PurposeEvaluation of the diagnostic performance of direct latex agglutination test (DLA), post-enrichment latex agglutination (LA) test, and direct culture on chromogenic media in rapid identification of GBS carrier in pregnant women in comparison with the conventional post-enrichment CDC-recommended culture method and further to estimate GBS carriage prevalence and its antimicrobial susceptibility.MethodsTwo hundred pregnant wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
2
3
0
1
Order By: Relevance
“…In the current study, we found that 25.89% (29/112) of the pregnant women who underwent the screening were colonized with GBS. These results were concordant with other studies carried out in Egypt such as the study done in Benha university hospital by Tash and co-workers (2019) which showed a prevalence rate of 28% [14], also another study was carried out by El Shahaway and colleagues (2019) at Zagazig university hospital which showed a prevalence rate of 23.5% [15]. Similarly, another study performed by Sadaka and his team (2017) at Alexandria reported a prevalence rate of 26.5% for GBS [16].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, we found that 25.89% (29/112) of the pregnant women who underwent the screening were colonized with GBS. These results were concordant with other studies carried out in Egypt such as the study done in Benha university hospital by Tash and co-workers (2019) which showed a prevalence rate of 28% [14], also another study was carried out by El Shahaway and colleagues (2019) at Zagazig university hospital which showed a prevalence rate of 23.5% [15]. Similarly, another study performed by Sadaka and his team (2017) at Alexandria reported a prevalence rate of 26.5% for GBS [16].…”
Section: Discussionsupporting
confidence: 91%
“…Heavy bacterial growth from vaginal swab in our study showed highest prevalence of S. agalactiae (18.8% of participants). Vaginal carrier rate of S. agalactiae among Egyptian pregnant females was reported in a previous study to be 23.5% [30]. In our study it was revealed in vaginal swab of 25% of pregnant females with PPROM.…”
Section: Discussionsupporting
confidence: 60%
“…GBS colonization in pregnant women is a major risk factor for neonatal and infant infections (Burcham et al, 2019). The most common epidemiological analysis of GBS infections is the latex agglutination (LA) assay using the specific surface capsular polysaccharide (CPS) antibodies for serologic typing (El et al, 2019). The commercial LA kits sometimes are unable to serotype the GBS isolates with low expression of CPS, methods for genoserotyping with both serotyping and PCR amplification of the capsular gene was developed accordingly (Poyart et al, 2007;Imperi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%